ANALYZING THE EFFECT OF FACTORS ON TAXPAYERS SATISFACTION USING E-FILING TAX REPORTING SYSTEM - Sebastian Prasetya Kresnandita; Levana Dhia Prawati; Lusiana (Journal of Applied Finance and Accounting, 2023)
The biggest source of state revenue comes from tax revenue. To increase tax revenue and simplify taxpayers in tax reporting, The Directorate General of Taxes introduced an application system namely Electronic Filing System (E-Filing). With this system, taxpayers don’t need to come directly to the Tax Service Office to fulfill tax obligations in terms of SPT reporting, because SPT reporting can be done online by accessing the E-Filing System. The purpose of this study is to analyze the relationship between system quality, information quality, and service quality with personal taxpayers’ satisfaction in using the E-Filing System for tax reporting. This study uses a quantitative approach. The use of the measurement model is the success model from DeLone and McLean (2003). The results of this study are system quality and information quality have significant effects on the user of personal taxpayers’ satisfaction using the E-Filing System, and service quality hasn’t a significant effect on the user of personal taxpayers’ satisfaction using the E-Filing System.